The Effect of Game on the Students’ Tense Achievment - Julien Arief Wicaksono; Gullit Tornado Taufan; Degita Danur Suharsono (LUNAR, 2021)
This research was conducted to investigate the effect of using game on the seventh-grade students’ tense achievement at SMPN 2 Balung-Jember. The primary data of this research were collected from the students’ scores of tense test. The primary data were collected from the post-test to compare the two different groups after treatment and analyzed the result by using independent sample T-Test (SPSS). Based on the calculation, the result of this research showed that there was a significant effect of using game on the seventh-grade students’ tense achievement. It was proved by the value of significant column of t-test table by using SPSS software, and the result was 0.045 which was lower than 0.05 (significant level of 5%). The research results proved that there was a significant effect of using game on the seventh-year students’ tense achievement at SMPN 2 Balung-Jember. Therefore, it is recommended for the English teacher to use game as an alternative technique in teaching tenses.